48. EVALUATION OF KNOWLEDGE, ATTITUDE AND PRACTICE OF COVID-19 PREVENTION AND CONTROL REGULATIONS AMONG PATIENTS AND THEIR FAMILY AT NATIONAL LUNG HOSPITAL AND ASSOCIATED FACTORS IN 2022 (Vietnam Journal of Community Medicine, 2024)
Objectives: The study aimed to evaluate the knowledge, attitude and practice of Covid-19 prevention and control regulations of inpatient patients/patients' family were treating at National Lung Hospital.Methods: A cross-sectional study on 200 patients/patients' family members during the period from February to March 2022.Results: The patients/patients' family members have the correct knowledge, attitudes and practices of prevention and control regulations Covid-19 were 88%, 45.5% and 83.5% respectively.Conclusion: The patients/family members did not correctly understand the meaning of epidemic prevention and control measures, but only take them because of the policies of the state and local authorities, so the proportion of people with knowledge and practice well is high, but attitude is only lower. Therefore, it is necessary to put in place measures for patients/ patients' family to really understand and voluntarily implement such prevention regulations instead of forcing them.
Keywords: Covid-19, knowledge, attitude, practice.